Determination of Static and Dynamic Yield Stress of Chengdu Clay Slurry - XianJun, Ji; Ying, Liang; WenHao, Cao; XiaoKang, Sun; Peng, Song (Frontiers in Physics, 2022)
The yield stress of mud is the key to analyze the initiation and deposition of landslide and debris flow. Chengdu clay was used as experimental material to prepare slurries with different volume concentrations. The stress sweep experimental method was carried out by using the blade rotor system of mcr301 rheometer to obtain the flow curves of slurries with different solid volume concentrations. According to the experimental results, the static and dynamic yield stress of Chengdu clay slurry are determined, and the influence of solid volume concentration on the yield stress is analyzed. The following conclusions are obtained: Chengdu clay slurry is a non-Newtonian fluid with yield stress. When the mud concentration exceeds 35%, the shear stress increases rapidly, then decreases rapidly, and finally tends to be stable; The maximum static yield stress appears near the shear rate of 1s-1, and the dynamic yield stress is the minimum shear stress of stable flow. When the mud concentration is less than 35%, the mud shear stress increases rapidly in the low shear rate area and remains basically stable. The dynamic and static yield stress values are consistent and appear near the shear rate of 0.1s-1. The static and dynamic yield stress of Chengdu clay slurry increases exponentially with solid volume concentration.